Membangun Jiwa Wirausaha dan Literasi Keuangan melalui Rumah Budaya Perpustakaan Bahagia Mendawai - Zailani Arbain; Anwar Azazi; Alfiyyah Misbahussaniyyah; Damia Raudhatusukma; Syifa Putri Damayanti; Nethlyn Vincyarif Guntur (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
This program aims to foster economic literacy and entrepreneurial spirit from an early age among children in Kampung Wisata Caping, Pontianak. Through a participatory approach, activities were carried out over 13 days, involving children in the creation of e-books, creative workshops, and practical trading exercises. The results demonstrate increased enthusiasm for learning, awareness of local potential, and the optimization of the library as a culturally-based educational space. This program is expected to serve as the first step toward sustainable empowerment for children.